Long-Range Capital Improvement Planning - Eddy J. Van Meter; G. Kent Stewart (Educational Considerations, 1976)
Capital improvement planning provides a regular program for budgeting and fiscal planning. A 6-year plan provides the luxury of reflection rather than stamping out fires in the heat of disaster.